2018
DOI: 10.3390/antib7040036
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Fusion of an Anti-BclA Single-Domain Antibody with Beta Galactosidase

Abstract: The Bacillus collagen-like protein of anthracis (BclA), found in Bacillus anthracis spores, is an attractive target for immunoassays. Previously, using phage display we had selected llama-derived single-domain antibodies that bound to B. anthracis spore proteins including BclA. Single-domain antibodies (sdAbs), the recombinantly expressed heavy domains from the unique heavy-chain-only antibodies found in camelids, provide stable and well-expressed binding elements with excellent affinity. In addition, sdAbs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Problems arise when combining peptides with incompatible fusion preferences, as was found to be the case in creating a series of diatom biosilica-targeted constructs encoding sdAbs against the B. anthracis S-layer protein EA1. In particular, both the Sil3 T8 (e.g., [12,15,16,32]) and sdAb EA1 (e.g., [33,34]) peptides previously have been made only as N-terminal fusions to their partners. One reason for this order of fusion partners is the requirement of many signal peptides' proximity to the protein terminus, rather than just their amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Problems arise when combining peptides with incompatible fusion preferences, as was found to be the case in creating a series of diatom biosilica-targeted constructs encoding sdAbs against the B. anthracis S-layer protein EA1. In particular, both the Sil3 T8 (e.g., [12,15,16,32]) and sdAb EA1 (e.g., [33,34]) peptides previously have been made only as N-terminal fusions to their partners. One reason for this order of fusion partners is the requirement of many signal peptides' proximity to the protein terminus, rather than just their amino acid sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several strategies have been described for increasing the stability of sdAb [37], and have been shown to increase melting temperatures by as much as 20 °C [43]. Similarly, sdAb can be engineered to tailor them for specific assay formats [28,32,55].…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial cytoplasm is a reducing environment that impairs the formation of the nanobody internal disulfide bond(s). However, several VHHs can fold into a functional structure independently on the presence of such disulfide bond(s) [49,102,103] and disulfide bond-independent nanobodies (intrabodies) were successfully produced in E. coli cytoplasm even when fused to large partners such cucurmosin toxin [104]. Since the preliminary results indicated that their anti-Bacilus anthracis nanobodies were stable and functional intrabodies, Anderson et al [103] expressed them fused to beta galactosidase directly in the cytoplasm of Tuner (DE3) E. coli.…”
Section: Bacterial Cytoplasmmentioning
confidence: 99%
“…However, several VHHs can fold into a functional structure independently on the presence of such disulfide bond(s) [49,102,103] and disulfide bond-independent nanobodies (intrabodies) were successfully produced in E. coli cytoplasm even when fused to large partners such cucurmosin toxin [104]. Since the preliminary results indicated that their anti-Bacilus anthracis nanobodies were stable and functional intrabodies, Anderson et al [103] expressed them fused to beta galactosidase directly in the cytoplasm of Tuner (DE3) E. coli. Shibuya et al [105] managed to coexpress in bacterial cytoplasm nanobodies fused to complementary split intein moieties for obtaining bispecific VHH constructs by in-cell transsplicing whereas nanobodies engineered with extra cysteines or ascorbate peroxidase were functionally recovered after production in NEB express F' cells [39].…”
Section: Bacterial Cytoplasmmentioning
confidence: 99%